A model of child life intervention to facilitate effective coping in a child hospitalized for heart surgery. (September 2013) - Dolidze, Khatuna; Smith, Emma; Tchanturia, Kate
SUMMARY This case study illustrates the effectiveness of providing developmentally appropriate medical information to a 7-year-old child hospitalized for heart surgery. The intervention involved support during medical procedures and educational and therapeutic medical play to enhance information processing during a medical encounter. Self-report and observational data was obtained for distress and coping behaviors, anxiety, emotional well-being and perception of intervention effectiveness before and after the child life intervention. The data shows reduced levels of noncompliance and disruptive behavior, demonstrating the effectiveness of the intervention in reducing stress associated with misinterpretation of hospital experiences and ineffective child–caregiver communication.